YRDC Mediates the Resistance of Lenvatinib in Hepatocarcinoma Cells via Modulating the Translation of KRAS - Guo, Jun; Zhu, Peng; Ye, Zhi; Wang, Mengke; Yang, Haijun; Huang, Shiqiong; Shu, Yan; Zhang, Wei; Zhou, Honghao; Li, Qing (Frontiers in Pharmacology, 2021)
Lenvatinib is the latest and promising agent that has demonstrated a significant improvement of progression-free survival in advanced hepatocellular carcinoma (HCC). However, resistance emerges soon after initial treatment, limiting the clinical benefit of lenvatinib. Therefore, understanding the mechanism of resistance is necessary for improving lenvatinib efficacy. YRDC promotes hepatocarcinoma cells proliferation via regulating the activity of RAS/RAF/MEK/ERK pathway, which was the primary pathway of anticancer effect of lenvatinib. The purpose of this study is to investigate whether and how YRDC modulates the sensitivity of lenvatinib in hepatocarcinoma cells. Using CCK-8 cell viability assay, wound-healing assay and clone formation assay in cell models, and xenograft assay in null mouse, we demonstrated that Huh7 cells with YRDC knockdown showed decreased susceptibility to lenvatinib than their control cells. Furthermore, we found that lenvatinib inhibited the expression of YRDC in time-dependent manner. This effect may aggravate resistance to lenvatinib in hepatocarcinoma cells and may be an underlying cause of resistance emerges soon after lenvatinib initial treatment. To investigate how YRDC modulates the sensitivity of lenvatinib, we assessed the effect of tRNA with different t6A level on translation of KRAS gene by In vitro rabbit reticulocyte translation system and measured the expression levels of KRAS by Western blot together with qPCR. We found that YRDC regulates the protein translation of KRAS in cell models, and the tRNA with low t6A modification level reduces the translation of KRAS in In vitro translation system. These results suggest that YRDC mediates the resistance of lenvatinib in hepatocarcinoma cells via modulating the translation of KRAS. In this study, YRDC was confirmed to be a potential novel predictive biomarker of lenvatinib sensitivity in HCC.